Preferensi Masyarakat Terhadap Pengolahan Sampah Organik Melalui Program Biopori Dan Komposter Berbasis Komunal Pada Kawasan Perumahan - Fitri Muliani; Aris Munandar; Ammar Fadhil (Fakultas Teknik - Universitas Al Muslim - Bireuen Aceh- Indonesia, 2025)
In order to ascertain the community's readiness to adopt organic waste management specifically, household waste through the composter and biopore programs. This study will analyze household waste management in the Komplek BTN Bukit Teukuh by using community preference analysis. It will do this by utilizing ordinal data from the SPPS application, which has a Multidimensional Scaling Analysis (MDS) feature. With 298 residents and 51 Heads of Families (KK), the study's focus is a housing area in the BTN Bukit Teukuh Complex, Kota Juang District, Bireuen Regency. Storage, collection, transfer, transportation, processing, and final disposal are just a few of the buildings and infrastructure that will be used in waste management activities. Composter and biopore technology are two technologies that can be used to overcome problems in organic waste processing through communal-based composter technology. Based on field observations that have been carried out, data was obtained that organic waste produced in the BTN Bukit Teukuh Complex with a total of 51 families (KK) is 0.3 to 0.45 kg/day in each house, so the total organic waste obtained is 22.95 kg/day. The results of the study in the form of MDS analysis showed that 89% of the community's preferences had implemented the container aspect, 77% the transportation aspect, 55% of the community participated in communal-based waste management, 45% the container aspect, and 10% the composter aspect.